2018
DOI: 10.21467/ias.5.1.26-32
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Growth Response of Three Jatropha Species on Heavy Metal Contaminated Soil

Abstract: A B S T R A C TThis study investigated the comparative phytotoxcity effect of heavy metal contamination on Jatropha curcas, Jatropha gossypifolia and Jatropha multifida in contaminated soil from a dump site in Ibadan Nigeria. Seeds of J. curcas, J. gossypifolia and J. multifida were planted in a germination tray and later transplanted into polythene pots filled with 2kg of either control soil or heavy metal contaminated soil, a 3 × 2 factorial experiment laid out in complete randomized design (CRD) replicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…It was observed that the post-harvest soil heavy metals for all the species was reduced correspondingly to what is reported in other studies [8,9,22], albeit not significantly in all the post-harvest pots. The low and insignificant reduction may be due to the high level of contamination in the soil as the plants may need more time beyond the three months the plants were monitored to get acclimatized to the toxic environment, the phytotoxic effect of the heavy metals on the three Jatropha species is already documented [23]. The analysis of heavy metals in the Jatropha plant's part shows that the Jatropha spp were found to be able to efficiently remove the studied metals in varying degree, cadmium, however, was not detected in the plant parts of the three Jatropha species.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that the post-harvest soil heavy metals for all the species was reduced correspondingly to what is reported in other studies [8,9,22], albeit not significantly in all the post-harvest pots. The low and insignificant reduction may be due to the high level of contamination in the soil as the plants may need more time beyond the three months the plants were monitored to get acclimatized to the toxic environment, the phytotoxic effect of the heavy metals on the three Jatropha species is already documented [23]. The analysis of heavy metals in the Jatropha plant's part shows that the Jatropha spp were found to be able to efficiently remove the studied metals in varying degree, cadmium, however, was not detected in the plant parts of the three Jatropha species.…”
Section: Discussionmentioning
confidence: 99%